Experimental Investigation on the Crack Evolution of Marine Shale with Different Soaking Fluids - Wang, Lei; Bi, Zhenhui; Zeng, Yijin; Yang, Guangguo; Guo, Yintong; Yang, Hanzhi (Frontiers in Earth Science, 2021)
Hydration induced cracks could promote the complexity of hydraulic fractures in marine shale gas reservoir. But the evolution process and forming mechanism has not been fully investigated. In this paper, Longmaxi marine shale were collected and immersed in three types of fluids (distilled water, fracturing fluid, and mineral oil) for more than 10 days. The spatial-temporal evolution of soaking fractures was recorded and analyzed. A fracture mechanical model was established, considering the effects of in-situ stress, fluid pressure, hydration stress, and capillary force. The promotion mechanism of hydration cracks in forming complex fracking network was discussed. Results showed that hydration fractures were extremely developed and evenly distributed in a state of network for specimens immersed in distilled water. For specimens soaked in fracturing fluid, the hydration cracks were moderately developed for the addition of anti-swelling agent. Fractures were rarely developed for specimens treated in mineral oil. The hydration fractures were mainly formed in the first 5 h and showed strong anisotropy. Cracks parallel to the bedding planes accounted for the vast majority, with a small proportion developed in vertical direction. Theoretical calculations indicated that the stress intensity factor (SIF) caused by hydration stress and capillary force was greater than the measured fracture toughness. The micro crack would probably propagate along bedding planes and grow up into macro horizontal fractures, which promoted the formation of crisscrossing fracture network in shale gas formation.